Urban Cloaca - Between Closeness and Denial - Nowak, Andrzej (Porównania, 2024)
This article aims to suggest some insights that could be gained from a kind of”reverse engineering” approach. By demonstrating how biological, political, social and scientific networks were interwoven at the time of the formation of a modern metropolis like London, the article aims to highlight the complex interconnectivity that is being “disentangled” in many places today. It seeks to draw attention to the often-invisible post-humanist connections that shape our lives and the lives of cities, while also acknowledging the potential challenges they may pose. The analysis of the reaction to the construction of the Warsaw water transportation network is intended to highlight the continuity of a certain type of criticism of modernity and the potential dangers it entails.